Testing of fabrics for use in alpine ski competition suits - Bardal, L. M.; Reid, R. (Procedia Engineering, 2012)
This paper describes the process of testing fabrics for use in alpine ski competition suits for the Norwegian national team. The main goal of the project was to indentify the aerodynamically best currently available fabric for use in Slalom, Giant Slalom and Super G/Downhill suits for the 2011/2012 competition season. A selection of fabrics were selected and tested in a wind tunnel on cylinder models of varying diameters and on an airfoil model. Additional measurements were performed with increased stretching in order to identify how this would alter the performance of the fabrics. The fabrics tested showed a large spread in critical velocity, minimum drag coefficient (CD) and supercritical drag characteristics, clearly illustrating the need to individualize fabrics for each of the alpine competition disciplines according to average race speeds. Full race suits were made from three of the fabrics and tested on athletes. These measurements confirmed the trend from the model measurements, although the variability in these measurements was too large to make a reliable estimate of actual drag reduction.